2019
DOI: 10.1016/j.siny.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional policies for late preterm and early term infants – can we do better?

Abstract: Late preterm (LP) and early term (ET) infants can be considered the "great dissemblers": they resemble healthy full-term infants in appearance, but their immaturity places them at increased risk of poor short-and long-term outcomes. Nutritional requirements are greater than for full-term babies, but there are few good data on the nutritional requirements for LP and ET babies, leading to substantial variation in practice. Recent data indicate that rapid growth may be beneficial for neurocognitive function but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 64 publications
0
14
0
2
Order By: Relevance
“…Suboptimal nutritional support is usual following major surgery of gastrointestinal tract, due to non-physiological feeding (commonly only intravenous and then only slow advancement of often dilute enteral feeding), as well as and increased protein synthesis for tissue repair, which is a high energy-requiring process [21]. In our study, we found that the median energy intake was frequently below or close to the minimum 90 Kcal/kg/d recommended for parenteral and enteral nutrition [38,39,45,46]; median energy intakes in infants born preterm varied between 80.7 and 115.8 Kcal/kg/d, and in infants born at term between 64.6 and 105.2 Kcal/kg/d. This resulted in periods of low energy balance, which varied between a median of 16.1 and 41.6 Kcal/kg/d in infants born preterm and 19.8 and 45.0 Kcal/kg/d in those born at term.…”
Section: Resting Energy Expenditure Energy Intake and Energy Balancementioning
confidence: 71%
“…Suboptimal nutritional support is usual following major surgery of gastrointestinal tract, due to non-physiological feeding (commonly only intravenous and then only slow advancement of often dilute enteral feeding), as well as and increased protein synthesis for tissue repair, which is a high energy-requiring process [21]. In our study, we found that the median energy intake was frequently below or close to the minimum 90 Kcal/kg/d recommended for parenteral and enteral nutrition [38,39,45,46]; median energy intakes in infants born preterm varied between 80.7 and 115.8 Kcal/kg/d, and in infants born at term between 64.6 and 105.2 Kcal/kg/d. This resulted in periods of low energy balance, which varied between a median of 16.1 and 41.6 Kcal/kg/d in infants born preterm and 19.8 and 45.0 Kcal/kg/d in those born at term.…”
Section: Resting Energy Expenditure Energy Intake and Energy Balancementioning
confidence: 71%
“…The LPT are usually not discharged from the hospital until they are at least 48 h old 17 . Prior to discharge, these infants should have been stable for at least 24 h. Clinical stability is established in terms of successful feeding for at least 24 h without excessive weight loss or vomiting; passing at least one stool per 24 h; having stable vital signs; and having no signs of sepsis 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Optimal nutrition might help to prevent or reduce the incidence of developmental deficits. In a study regarding nutritional policies, breastfeeding was advised as the most optimal feeding for the late preterm infant (Muelbert et al, 2019). There is a lack of well-executed studies, however, that evaluate the optimal composition of nutrition, such as the amount of protein late preterm infants require.…”
Section: Discussionmentioning
confidence: 99%